The Position of Banggai Women in The Myth and Reality - Samatan, Nuriyati; St. Samsuduha; Maryati; Robingah (Journal of Law, Politic and Humanities, 2023)
The study aims to conduct an analysis of Banggai women position in the myth and reality. The social role theory was applied. A chronological approach was taken by describing events unfolding slowly following the process of time to examine the position of Banggai women in myth and reality. The method applied was qualitative with narrative, using a chronological approach across the time. The data were collected through documentation, FGD, observations and in-depth interviews. The result found that there were significant differences between Banggai women in myth and reality. In myth, Banggai women are placed in a decisive position in the family and in society, while in reality, they are in a subordinate position, comparing to men, both in the family and in society. Based on the results of the analysis, it was found that women's social roles were influenced by various things. Novelty: This study used a narrative approach in analyzing the Banggai women in myth and reality